Demographic dividend, economic and employment growth in Indonesia - Maryam, St; Hailuddin, Hailuddin; Endri, Endri (International Journal of Innovative Research and Scientific Studies, 2025)
The research aims to measure and analyze the relationship between growth and employment growth according to the economic sector in Indonesia, using secondary data for 2019-2023: variable economic growth and employment growth in Indonesia. Research data comes from the Central Statistics Agency of Indonesia. The descriptive quantitative analysis method uses the Coefficient of Employment Opportunity Elasticity with Elastic, Unitary, and Inelastic criteria. The study found that the employment opportunity coefficient for all economic sectors during the analysis period was inelastic, where the elasticity figure was less than one. The higher the elasticity of job opportunities, the greater the ability of the economic sector to create employment due to economic growth. The high elasticity of jobs means that the economic sector can absorb labor with the value-added sector and vice versa. Employment opportunity elasticity of less than one indicates the low ability of each economic sector to absorb labor in that sector. The demographic bonus era for each region is different; some districts or cities precede entering the demographic bonus era compared to the arrival of the bonus era at the provincial level. The bonus can come very slowly because a district with a large population has yet to enter the bonus era.